Plant Growth–promoting Rhizobacteria Have Varied Effects on Quality and Yield of Drought-stressed Creeping Bentgrass (Agrostis stolonifera) - Paige E. Boyle; David Held; Kelly Kopp; Xin Dai (HortTechnology)
Recently, there has been renewed interest in reducing excess inputs into turf, with a special emphasis on reducing water use. One potential mechanism to achieve this goal is the use of plant growth–promoting rhizobacteria (PGPR) applications. Plant growth–promoting rhizobacteria research in turfgrass is limited, but the few studies that have been conducted show that PGPR can reduce biotic and abiotic stress in turfgrass. Two creeping bentgrass (Agrostis stolonifera) cultivars (Penncross and 007) were treated with either PGPR Blend 20, PGPR DH44, water, or nitrogen fertilizer before being subjected to a dry-down period during which half of each treatment was either irrigated or drought stressed. Results indicate that PGPR DH44 may help maintain greater quality in drought-stressed ‘007’ creeping bentgrass compared with nitrogen-treated plots; however, quality did not differ between DH44- and water-treated plots. When drought stressed, PGPR did not help creeping bentgrass maintain clipping yield compared with nitrogen-fertilized or water-treated plots, nor did PGPR affect root biomass. More research is needed before recommendations can be made regarding PGPR applications to turfgrass.